The Causal Relationship between, Electricity Consumption and Economic Growth in Kingdom of Saudi Arabia: A Dynamic Causality Test - Belal, Ibrahim Abdelrasoul Mohammed; Ahmed, Sumaya Awad Khader; Boujedra, Faouzi Hedi (International Journal of Energy Economics and Policy, 2020)
The main objective of this study is to empirically test whether there exist short run and long run causality between, Residential Electricity Consumption (REC), Industrial Electricity Consumption (IEC) and economic growth in Kingdom of Saudi Arabia (KSA). Time series data for this study spans from 1990 to 2019. The study adopts granger causality and co. Integration analysis to estimate a Vector Error Correction Model (VECM). Results from error correction model show that there exist long run co. integration relationship between targeted variables. In addition, VECM results indicates that, industrial electricity consumption is inelastic to the changes in electricity prices with respect to economic growth, while residential electricity consumption shows elastic relationship. Granger causality test indicates there is unidirectional relationship, running from economic growth to industrial electricity consumption, which lead to accept, proactive (conservative) hypothesis. In this case, energy conservative policy will have little or no effect on economic growth. Nevertheless, results proof acceptance of neutrality hypothesis in the case of residential electricity consumption and economic growth. The study therefore, recommends that in Saudi Arabia, policy makers should consider expanding their energy-mix alternatives, in order to cope with the future industrial electricity demand arising from increased economic growth. Keywords: electricity consumption, GDP growth, co. integration and causality. JEL Classifications: O3, O4 DOI: https://doi.org/10.32479/ijeep.10488